2011
DOI: 10.4081/nursrep.2011.e4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of communication behavior in persons with dementia during caregivers’ singing

Abstract: The number of persons with dementia (PWD) is increasing rapidly worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 49 publications
2
20
1
Order By: Relevance
“…If compared with previous single case studies with MTC [21,22] , the result of this study is faint since MTC was shown to radically improve communication [22,23,27] and positive emotions [19,21] . The decision to instruct the caregiver to hum instead of sing might have been a disadvantage, since the singing might have been preferable.…”
Section: Reflections On the Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…If compared with previous single case studies with MTC [21,22] , the result of this study is faint since MTC was shown to radically improve communication [22,23,27] and positive emotions [19,21] . The decision to instruct the caregiver to hum instead of sing might have been a disadvantage, since the singing might have been preferable.…”
Section: Reflections On the Resultscontrasting
confidence: 58%
“…This procedure is repeated until all ten-one minute segments are scored. Reliability and validity was supported in a previous study of individuals with Alzheimer's disease and their spouse caregivers [27,28] .…”
Section: The Instrumentmentioning
confidence: 66%
See 1 more Smart Citation
“…Nearly all art forms offer people with dementia and carers opportunities for creative expression, skill development, cognitive and emotional stimulation, and non-stigmatising social engagement. In particular, research involving singing ( Engström et al , 2011 ; Särkämö et al , 2013 ), music ( Ragneskog et al , 2001 ; van der Vleuten, 2012 ), visual arts ( Camic et al , 2016 ; Windle et al , 2014 ) and museum programmes ( Camic et al , 2017 ; Johnson et al , 2017 ) have shown promising initial findings.…”
Section: Background and Rationalementioning
confidence: 99%
“…Finally, there are several situations in which singing enhances communication with specific client groups. For example, music-embedded conversations involving singing instead of talking enhance communication between caregivers and people with dementia (Beer, 2016;Engström, Marmstål, Williams, & Götell, 2011;Hammar, Emami, Engström, & Götell, 2011), and also between teachers and children with ASD (Braithwate & Sigafoos, 1998). Although it is not completely clear which mechanisms are at work here, enhanced perceptiveness for language through music may play a part.…”
mentioning
confidence: 99%